Caticlan cruise terminal a transition to Boracay Island - Ong, Arra Christine L.
Philippine cruise industry is taking a leap and joining the world cruise industry. as an archipelagic country, we are blessed with numerous islands that can cater the cruise tourism industry. However, with abundance of tourst islands, the Philippines is lacking facilities that would cater the hospitality and travel needs of the tourists. One of the most travelled tourist destination in the country is the island of Boracay. Caticlan Cruise Hub is proposed to provide a transition space for tourists from across the sea to Caticlan then to Boracay Island. Studies were conducted such as project background, site analysis, architectural programming, and design schematics for the development. The Caticlan Cruise Hub, based on the information gathered and analysis, consists of a cruise terminal, a mini hotel, an intermodal zone and parking area. These facilities are integrated to each other for a spontaneous movement of travelling tourists.